PENGEMBANGAN KEWIRAUSAHAAN DI DESA TAPULAGA UNTUK PENINGKATAN PENDAPATAN MASYARAKAT - Yusuf; La Ode Asfahyaddin; Muhammad Taufik (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2024)
The aim of this community service is to help the Tapulaga village community increase their business income through financial management by preparing simple financial reports and to help the community increase sales of community businesses in Tapulaga Village through online marketing. The implementation method is carried out by means of counseling and training in 22 Tapulaga village communities. The implementation of this service shows that the community still has difficulties in managing finances and sales are still limited to the sales area in Tapulaga village. It is hoped that after community service they will be able to implement the results of counseling and training well.